Application of BP neural network in evaluating e-business performance for service industry. (1st January 2012) - Chi, Maomao; Zhao, Jing
The BP neural network model has a convergence and self-adaptability. Based on BP neural network algorithms, we establish the prediction system of e-business performance for Chinese service industry. According to our former studies, the e-business performance is measured by process performance of customer relationship management, financial performance and competitive performance. In this BP neural network model, the inputs in this study are the data of e-business performance measured by a five-point Likert scale, and the expected outputs of training neural network come from cluster analysis. Then, we take 14 indicators of e-business performance as inputs, and the level of e-business performance as outputs. The results show that the evaluation system is reliable and accurate; it can be used for evaluating enterprise performance effectively.